The immunomodulatory effects of fish-oil supplementation in elite paddlers: A pilot randomized double blind placebo-controlled trial. (August 2015) - Delfan, Maryam; Ebrahim, Khosro; Baesi, Fatemeh; Mirakhori, Zahra; Ghalamfarsa, Ghasem; Bakhshaei, Peyman; Saboor-Yaraghi, Ali Akbar; Razavi, Alireza; Setayesh, Maryam; Yousefi, Mehdi; Jadidi-Niaragh, Farhad
Abstract: Background: Physical exercise can induce imbalance of different cytokines by leading them towards an inflammatory and immunosuppressive milieu. Fish-oil (FO) supplementation may modulate the mentioned skewed balance following intense exercise. Therefore, we decided to investigate the effect of intense physical exercise and FO supplementation on cytokine production and helper T (Th) cell phenotype in male elite paddlers. Subjects and methods: Male elite paddlers consumed 6 g/day of either FO capsules ( n =11) containing 3.6 g long chain n-3 polyunsaturated fatty acids (1.2 g docosahexaenoic acid and 2.4 g eicosapentaenoic acid) or placebo capsules ( n =11) for 4 weeks. The paddlers simultaneously undertook a program of increasing exercise. Blood samples were taken from all the subjects 48 h before and after the 4 weeks of supplementation. Results: Our results show that while FO supplementation decreases the production of tumor necrosis factor (TNF)-α and interleukin (IL)-1β in the elite paddlers, it increases the production of IL-6. On the other hand, while there was no change in IL-4 secretion, the production of interferon (IFN)-γ was significantly decreased after 4 weeks FO consumption. We also showed that the production of IL-10 was significantly higher in the FO group compared to the placebo. Finally, we found that fish-oil consumption shifts the balance between Th cells towards Th2 phenotype during intensive exercise. Conclusion: Our results suggest that the consumption of n-3 polyunsaturated fatty acids during intense exercise can induce the anti-inflammatory and immunosuppressive cytokine networks that are associated with a reduced Th1/Th2 ratio in elite paddlers.